Tribological challenges in press hardening - Schwingenschlögl, Patrik; Merklein, Marion (Stahl und Eisen, 2019)
Hot stamping has established as a common technology for manufacturing safety-relevant components in modern vehicle bodies. By applying thin sheet thicknesses, using hot stamped parts offers the chance of improving crash performance while towering the mileage. The most commonly used material for hot stamped components is the high-strength-steel 22MnB5. In order to avoid the formation of oxide scale during the heat treatment and the subsequent forming process, an AISi coating is applied to the boron-manganese-steel. Due to the forming temperatures between 600 °C and 850 °C, no suitable lubricants have been found yet. Thus, high friction and severe wear occur during the forming. This has an impact on the resulting part quality as well as the tool lifetime. As a consequence, future measures that reduce the tribological loads have to be found in order to improve the robustness and the efficiency of industrial hot stamping applications. Within this study, friction and wear are characterized for different workpiece and tool temperatures, relative velocities and contact pressures. Based on the experimental results, suggestions regarding the process design of hot stamping applications will be given.
CRIS-Team Scopus Importer:2021-04-20